Spectral chores. Pablo Katchadjian and the avant-garde today (Anclajes, 2020)
In a historical period that has decreed the end and the impossibility of the avant-garde, some writers recover that tradition and displace its definitions. In Argentina, Pablo Katchadjian's "beginnings" were characterized by a series of spectacular interventions and an extension of the experimental.  In the article I intend to delimit the problems of these anachronistic avant-gardes by proposing a reading of the author's strangest book, the novel Qué hacer (2010). The structural combinatorial, the relationship with the literary past, the exacerbated formalism and certain representations of time, among other elements, seem to answer the question posed by the title: how to do in order to continue writing. In Katchadjian, writing continues thanks to a renewed and traditional effect of hallucinatory estrangement.
Keywords: Argentine literature; Pablo Katchadjian; experimental literature; avant-garde